1999
DOI: 10.1046/j.1365-3156.1999.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme‐linked immunosorbent assay for detection of IgG1 antibodies specific to human cystic echinococcosis in Egypt

Abstract: SummaryHuman cystic hydatidosis (cystic echinococcosis) is a chronic zoonotic disease that results from infection with the dog tapeworm Echinococcus granulosus. In Egypt, cystic echinococcosis (CE) is recognized in slaughtered livestock by veterinarians, however, there is little information about human CE infection rates. We describe an immunological assay useful for the diagnosis of human cystic hydatidosis. Sera were collected from surgically confirmed hydatid cases (34), nonendemic subjects free from parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…An enzyme-linked immunosorbent assay or indirect haemagglutination test is commonly used as an initial screen, and is positive in onlyy50% of patients with pulmonary hydatidosis and w90% of patients with hepatic cysts [38]. Testing for specific antibodies, such as specific immunoglobulin G1 or G4 rather than total immunoglobulin G, may improve the specificity of a test [39,40]. The specificity of these tests increases considerably when utilising antigen 5 (arc 5 test), immunoblotting or gel diffusion assay for specific hydatid antigen.…”
Section: Laboratory and Special Investigationsmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay or indirect haemagglutination test is commonly used as an initial screen, and is positive in onlyy50% of patients with pulmonary hydatidosis and w90% of patients with hepatic cysts [38]. Testing for specific antibodies, such as specific immunoglobulin G1 or G4 rather than total immunoglobulin G, may improve the specificity of a test [39,40]. The specificity of these tests increases considerably when utilising antigen 5 (arc 5 test), immunoblotting or gel diffusion assay for specific hydatid antigen.…”
Section: Laboratory and Special Investigationsmentioning
confidence: 99%
“…In humans there is frequent occurrence of elevated antibody levels, particularly of the IgG, IgM, and IgE isotypes (46,52,64,113,114,197,206,243). In seropositive individuals, there tends to be a predominance of IgG1 and IgG4 antibody recognition of antigen 5 (Ag5) and antigen B (AgB) (see below), respectively (2,52,129,233,243,258).…”
Section: Established Cystsmentioning
confidence: 99%
“…Bovine HCF can be used as an alternative antigen source; indeed, it can improve diagnostic sensitivity (130,206). HCF of camel origin has also been used as antigen in an ELISA format to measure total E. granulosus-specific IgG antibodies and IgG subclasses (206 (185), the major components of HCF, have received the most attention with regard to diagnosis. Along with HCF, they are the most widely used antigens in current assays for immunodiagnosis of CE.…”
Section: Immunodiagnosis Of Cystic Echinococcosis In Humansmentioning
confidence: 99%
“…The cross-reactivity between EG and F. hepatica infection has been reported previously (11)(12)(13). Parasitic helminths express some antigen, which often accounts for serological cross-reactions.…”
Section: Introductionmentioning
confidence: 65%
“…Wuhrer et al (15) reported that F. hepatica exhibits mammalian-type glycolipids as well as Gal (ß1-6) Gal-terminating glycolipids that account for cestode serological cross-reactivity. Ramzy et al (12) reported that 5% of healthy people have IgG3 antibody and 10% of healthy people have IgG4 antibody for EG. Cross-reactivity has been observed with total IgG antibody followed by that of IgG4 in the sera from cases with trichostrongyliasis, ancylostomiasis, schistosomiasis, ascariasis, and fascioliasis.…”
Section: Discussionmentioning
confidence: 99%